Theory of Constraint and Drum Buffer Rope Increase Shoe Production Throughput: Teori Kendala dan Drum Buffer Rope Meningkatkan Produktivitas Produksi Sepatu - Rahmawati, Dea; Rochmoeljati, Rr. (Indonesian Journal of Innovation Studies, 2026)
General Background: Production systems frequently experience capacity imbalances that disrupt material flow and reduce throughput, particularly in small- and medium-scale manufacturing environments. Specific Background: UD Anugrah, a footwear manufacturer specializing in children’s shoes, faces recurring work-in-progress accumulation caused by unequal capacities among production workstations. Knowledge Gap: Prior studies have widely applied the Theory of Constraints, yet empirical applications integrating Drum-Buffer-Rope scheduling within the footwear manufacturing sector remain limited. Aims: This study aims to optimize production capacity at UD Anugrah by applying the Theory of Constraints integrated with the Drum-Buffer-Rope concept to identify, manage, and resolve system bottlenecks. Results: Sewing and Injection workstations were identified as primary constraints; optimization through linear programming, flow synchronization, and selective capacity elevation increased monthly throughput from IDR 88,166,810 to IDR 91,707,000, representing a 3.86% increase, while financial analysis yielded a positive Net Present Value of IDR 61,881,704 and a Payback Period of 3.41 years. Novelty: This research presents an integrated TOC–DBR application within a shoe manufacturing context, supported by quantitative throughput and investment feasibility analysis. Implications: The findings demonstrate that structured constraint management and DBR-based flow control provide a practical framework for improving production performance and investment decision-making in small- and medium-scale manufacturing enterprises. Highlights: Sewing and Injection stations were consistently identified as system constraints across multiple production periods. Linear programming supported optimal product mix allocation under limited workstation capacity. Financial evaluation confirmed that selective machine addition was economically feasible within the system lifespan. Keywords : Theory of Constraints, Drum Buffer Rope, Production Capacity, Shoe Manufacturing, Bottleneck Analysis